PENGARUH ANTRAKNOSA (COLLETOTRICHUM CAPSICI DAN COLLETOTRICHUM ACUTATUM ) TERHADAP RESPONS KETAHANAN DELAPAN BELAS GENOTIPE BUAH CABAI MERAH (CAPSICUM ANNUUM L) - Mohamad Agus Salim (JURNAL ISTEK, 2012)
Anthracnose is a major disease that causes low productivity of red pepper plant in Indonesia. Anthracnose from Colletotrichum genus as the main cause of damage to the red pepper. This study to determine the response of red pepper to the infection of Colletotrichum capsici and C. acutatum. The experiments are conducted using a randomized block design with two factors and two replications. The first factor is the two species of fungi that cause anthracnose disease of C. capsici and C. acutatum whereas the second factor is 18 of genotype number of red pepper. The results showed that the development of C. capsici on red pepper are seen from the average of diameter growth of lesions more rapidly than C acutatum. The red pepper with genotype number 10 is the most resistant and genotype number 12 is the most susceptible to C. capsici infection.. The red pepper with genotype number 16 is the most resistant and genotype number 7 is the most susceptible to C acutatum infection.